Efektivitas Krim Anti Jerawat Kayu Secang (Caesalpinia sappan) Terhadap Propionibacterium acnes pada Kulit Kelinci - SITI SA’DIAH; LATIFAH KOSIM DARUSMAN; WULAN TRIWAHYUNI; IRMANIDA BATUBARA (Fakultas Farmasi Universitas Pancasila, 2013)
Sappan Wood extract (Caesalpinia sappan) is potential as an anti-acne due to its ability as an antioxidant, lipase inhibitor and anti Propionibacterium acnes. The potency is influenced by the quality of simplicia and extracts. To elevate the application, semisolid dosage formulations were made in cream forms using a standardized extract of Sappan Wood. Creams were formulated with the same base composition but different extract concentrations (range of 1-10%). In vivo assay were carried out on rabbit skin induced by intradermal injection of P. acnes. Sappan Wood was collected from Semarang and the resulting extract has met the Materia Medika Indonesia requirement with brazilin level in extract of 224.675 mg / g. In vivo tests showed that all Sappan Wood extract formulations have potency as anti-acne as indicated by curative percentage for 15 days were significantly different from the formula base. Curative effect of all formula were not significantly different with the Mediklin® positive control. Formula with the lowest concentration of the extract was the most effective and efficient with the curative percentage of more than 96% in 15 days.